Determinant of ETF Sharia Performance and the Moderating Role of Fund Size - Abadiyah, Fajriyatul (The Indonesian Capital Market Review, 2024)
The aim of this research is based on the potential and development of sharia investment products on the Indonesia Stock Exchange, namely the Sharia Exchange Traded Fund in recent years. Sharia ETFs are mutual funds that can be traded on the capital market like shares whose performance adheres to a sharia reference index. Having a hybrid composition that combines the performance of mutual funds and the practicality of shares, makes Sharia ETFs have a special attraction for investors. This research tries to examine the determining factors of fund performance traded on the Islamic exchange which include tracking error, trading volume, index volatility with fund size (AUM) as a moderating variable. Ordinary Least Square (OLS) analysis and moderation analysis (MRA) are used to answer the problem formulation using the Common Effect Model (CEM) approach. The research results show that in the multiple regression results, tracking error and index volatility have a significant negative effect on the performance of sharia ETFs, while trading volume does not have a significant effect on the performance of sharia ETFs. Furthermore, in the moderation analysis, the statistical results concluded that fund size was not able to moderate the relationship between tracking error and Sharia ETF performance, but fund size was able to moderate it in the direction of strengthening the relationship between traded volume and Sharia ETF. performance, but weakens the relationship between index volatility and Sharia ETF performance.